Spectrum of Renal Tumors Other Than Renal Cell Carcinoma with Emphasis on Cytomorphological, Immunohistochemical, and Cytogenetic Study - Soumya Alashetty; Priya Dharmalingam; Sindhu Ramamurthy; Bidadi Lingappa Kavitha; Siddappa Shanthala; Rajasab Subhan Ali (Journal of Cytology)
Background: The role of fine needle aspiration cytology (FNAC) in the diagnosis of renal malignancies is established and has been getting more precise and important over a period of time. Knowledge of the pathology of uncommon renal neoplasms along with radiological and clinical correlations often aids in correct diagnosis. Aims: The present study aims to describe the cytomorphological and immunohistochemical findings in the varied spectrum of renal tumors, other than renal cell carcinomas (RCC). Materials and Methods: Data of 238 cases of ultrasound-guided renal FNAC performed in our tertiary cancer institute over 4 years were collected from the department registry. All nondiagnostic cases and cases diagnosed as RCC were excluded from the study, so 57 cases of renal tumors were reviewed along with the cell blocks and ancillary studies. Results: Out of the 57 cases, 35 cases were primary renal neoplasms, which included renal oncocytoma (3.5%), angiomyolipoma (3.5%), rhabdoid tumor (1.8%), Wilms tumor (28.0%), Ewing sarcoma (3.5%), urothelial carcinoma (8.8%), and small round cell tumor unclassified (12.3%). Twenty two cases were metastatic tumors, which included hematolymphoid neoplasm (14%) and metastatic carcinomas (24.6%) from various other primary carcinomas. Conclusion: Our study shows that renal FNAC is safe and fairly accurate in diagnosing a wide spectrum of renal tumors and has high diagnostic accuracy, when performed along with cell block and immunohistochemistry. Awareness of the pathology of uncommon renal tumors along with relevant clinical history and radiological findings may aid in identifying the type of tumor for further appropriate management.